Initial Handling Of Tuna As Raw Material For Canned Fish - Handri Badoa; Jenki Pongoh; Hens Onibala; Eunike L. Mongi; Josefa Tety Kaparang; Daisy Monica Makapedua (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2023)
This study aims to determine histamine levels and organoleptic results from fresh tuna and frozen tuna. The data obtained are presented in the form of histograms and tables are then discussed. The results showed that histamine levels in 3 fresh tuna samples, namely S1, S2, and S3 samples, were below 30 ppm. 3 samples of frozen tuna, namely samples B1, B2, and B3, are also below 30 ppm which is the standard set by the company. This shows that samples from fresh tuna have a lower amount of histamine levels than frozen tuna, so they still meet the export standards of the Food and Drugs Administration (FDA) which is 50 ppm (FDA, 2011) and meet the Indonesian National Standard, SNI 2729: 2013 (BSN, 2013) which is a maximum of 100 ppm. For organoleptic results on 3 samples of fresh tuna and frozen tuna, namely samples 1, 2, and 3 showed organoleptic results from the appearance of the eyes, gills, appearance of body surface mucus, organoleptic results of meat, organ results of odor, organoleptic results of texture have a good value . This shows that samples from fresh tuna and frozen tuna are of good quality and still meet the Indonesian National Standard (SNI 2729:2013) regarding sensory criteria in fish. Keywords: Fresh Tuna, Frozen Tuna, Histamine, Sensory Abstrak Penelitian ini bertujuan mengetahui kadar histamin dan hasil organoleptik dari ikan tuna segar dan ikan tuna beku. Data yang diperoleh disajikan dalam bentuk histogram dan tabel kemudian dibahas. Hasil penelitian menunjukkan bahwa kadar histamin pada 3 sampel ikan tuna segar yaitu sampel S1, S2, dan S3 dibawah 30 ppm. 3 sampel ikan tuna beku yaitu sampel B1, B2, dan B3 juga dibawah 30 ppm yang merupakan standar yang ditetapkan perusahaan. Hal ini menunjukan bahwa sampel dari ikan tuna segar memiliki jumlah kadar histamin yang lebih rendah dari pada ikan tuna beku, sehingga masih memenuhi standar ekspor dari Food and Drugs Administration (FDA) yaitu 50 ppm (FDA, 2011) dan memenuhi Standar Nasional Indonesia, SNI 2729:2013 (BSN, 2013) yaitu maksimal 100 ppm. Untuk hasil organoleptik pada 3 sampel ikan tuna segar dan ikan tuna beku yaitu sampel 1, 2, dan 3 menunjukan hasil organoleptik dari kenampakan mata, insang, kenampakan lendir permukaan badan, hasil organoleptik daging, hasil organoleptik bau, hasil organoleptik tekstur memiliki nilai yang baik. Hal ini menunjukan bahwa sampel dari ikan tuna segar dan ikan tuna beku memiliki kualitas baik dan masih memenuhi Standar Nasional Indonesia (SNI 2729:2013) tentang kriteria sensori pada ikan. Kata Kunci: Tuna Segar, Tuna Beku, Histamin, Sensori